Nonsurgical Management of Severe Osteonecrosis of the Knee in an HIV-Positive Patient: A Case Report - Stephanie A. Nixon; Kelly K. O'Brien; Gary Rubin (Case Reports in Infectious Diseases)
Due to the life-prolonging effects of combination antiretroviral therapy, many people with HIV are living longer. However, this enhanced longevity is often mirrored by increased disability resulting from HIV and/or the adverse effects of medication. Management of HIV-positive patients is further complicated by comorbidities related to aging, including bone and joint disorders. In this paper, we describe the nonsurgical management of an HIV-positive patient with premature onset of severe osteonecrosis of the knee. A 50-year-old man who had been HIV-positive for 16 years and on combination antiretroviral therapy for 11 years presented to his family physician with extreme discomfort in his right knee. He was diagnosed with osteonecrosis of the right knee, but resisted total knee arthroplasty because of potential complications under anesthesia related to comorbid advanced liver disease. Instead, a successful combination of non-surgical management strategies was employed by the patient and his health care team.